Chapter Il secondo Ottocento italiano visto dalla Francia - Comoy Fusaro, Edwige (Biblioteca di Studi di Filologia Moderna, 2022)
This study examines the current reception of second part of the 19th century Italian literature in France. The data come from 4 sources of information: the general book market on foreign literature, the scholarly book market on Italian literature, the programs of Literature in Bachelor and Master curricula of Italian Studies, and the yearly programs of the competitive exam for teachers in Italian (Agrégation). As a result, the champion of second 19th century Italian literature's reception in French culture is Giovanni Verga, the traditional canon is mostly undiscussed but lately, both large audience publishing and academic studies show interest for relatively forgotten authors such as Grazia Deledda and movements such as Scapigliatura.